Investigating Knowledge of Indonesian Pre-service Science Teachers on the Greenhouse Effect Issue - Mannan, Muhammad Nur; Efwinda, Shelly; Subagiyo, Lambang; Hakim, Abdul; Khotimah, Siti Qusnul; Andrian, Ricky (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Teacher education institutions must pay attention so that future teachers have a strong and correct concept to teach actual knowledge to their students. This study explores Indonesian pre-service science teachers’ (PSTs’) knowledge of the Greenhouse Effect (GHE). The research participants were 187 Indonesian PSTs. The sampling technique used in this study was purposive sampling. The research instrument used was a questionnaire survey of 24 knowledge questions with three answer choices (true, wrong, or do not know) and two open questions. The PSTs’ knowledge data were analyzed through statistics and the Mann-Whitney test. The results of the data analysis showed that PSTs’ knowledge was in a low category, with an average score of 66.82. There was no significant difference between the knowledge of junior (2nd and 4th semester) and senior (6th and 8th semester) PSTs shown by a significance value of 0.445 > 0.005. Our findings also show that their knowledge of this issue is only superficial; for example, most of them mentioned that they had learned about the GHE process, but their explanations of how the GHE occurs were not detailed. Therefore, Institutions must strengthen their curriculum to equip PSTs with accurate and actionable knowledge of the GHE.